PENGARUH VIDEO PIJAT ENDHOPRIN TERHADAP KELANCARAN ASI PADA IBU MENYUSUI - Dewi Andariya Ningsih; Warda Anil Masyayih; Tiara Indriani; Susiana Susiana; Umi Nur Kholifah; Siti Romlah (LPPM Universitas Abdurrab, 2023)
Early and exclusive breastfeeding can help reduce infant mortality, which is still high in Indonesia. One of the reasons for the low coverage of exclusive breastfeeding for infants under six months of age is the delay in the production of postpartum mother's milk in the first days after giving birth so that most babies receive formula milk. multimedia learning. The purpose of this study was to determine the effect of multimedia video media on mother's knowledge about endorphin massage and breastfeeding smoothness. This research is a quasi-experimental research (one group pretest and posttest design). It was carried out between April and July 2021. The breastfeeding mothers in this study came from the Arjasa Health Center, Arjasa District, Situbondo Regency. Purposive sampling was used in sampling. The purpose of this study was to analyze the knowledge of breastfeeding mothers about endorphin massage through video learning multimedia of endorphin massage for smooth breastfeeding with the results that there was an effect before and after being given a video on knowledge of endorphin massage. Researchers suggest that health workers be more proactive in conducting media outreach activities with a family-centered approach.